2021
DOI: 10.1007/s00426-021-01519-0
|View full text |Cite
|
Sign up to set email alerts
|

Auditory and visual short-term memory: influence of material type, contour, and musical expertise

Abstract: Short-term memory has mostly been investigated with verbal or visuospatial stimuli and less so with other categories of stimuli. Moreover, the influence of sensory modality has been explored almost solely in the verbal domain. The present study compared visual and auditory short-term memory for different types of materials, aiming to understand whether sensory modality and material type can influence short-term memory performance. Furthermore, we aimed to assess if music expertise can modulate memory performan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 92 publications
(131 reference statements)
1
19
0
Order By: Relevance
“…However, cognitive advantages to musicians have not been consistently demonstrated and it may be that these effects are due to people with higher cognitive scores taking or persisting with music lessons or that there are links to preexisting innate interindividual differences 10 , 11 . There is evidence to suggest that musicians have better memory over shorter time scales than non-musicians and that this effect is moderated by the type of stimuli 12 . Although some studies have shown that musicians outperformed non-musicians in tasks of visual working memory, this has not been consistently demonstrated.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, cognitive advantages to musicians have not been consistently demonstrated and it may be that these effects are due to people with higher cognitive scores taking or persisting with music lessons or that there are links to preexisting innate interindividual differences 10 , 11 . There is evidence to suggest that musicians have better memory over shorter time scales than non-musicians and that this effect is moderated by the type of stimuli 12 . Although some studies have shown that musicians outperformed non-musicians in tasks of visual working memory, this has not been consistently demonstrated.…”
Section: Introductionmentioning
confidence: 99%
“…The authors concluded that working memory updating abilities might improve via sustained engagement in music. Auditory working memory for tones is an explicit cognitive task that has been examined in a number of studies in which improved performance is shown in groups of musicians compared to non-musicians 12 , 17 , 18 . Musicians have also been shown to have improved sustained attention and attention to pitch direction, as well as better general auditory cognition in terms of phonological working memory and speech-in-noise perception 19 22 .…”
Section: Introductionmentioning
confidence: 99%
“…According to models of auditory memory (Atkinson & Shiffrin, 1968;Christophel et al, 2017), the pattern to memorise may be firstly stored in a auditory-specific sensory memory store with high fidelity, and then transferred to a distributed network of brain areas involved in more abstract representations (e.g., of the contour). This second stage may be more dependent on listeners cognitive ability, encoding strategies, expertise and attention (Cowan, 2008;Talamini, Altoè, Carretti, & Grassi, 2017;Talamini et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…It has been argued that the effect of musical sophistication on perceptual tasks is determined by cognitive abilities (Ahissar et al, 2009). Auditory working memory for tones is an explicit cognitive task that has been examined in a number of studies in which improved performance is shown in groups of musicians compared to non-musicians (Ding et al, 2018; Talamini et al, 2021; Williamson et al, 2010). Musicians have also been shown to have improved sustained attention (Carey et al, 2015) and attention to pitch direction (Ouimet et al, 2012), as well as better general auditory cognition in terms of phonological working memory and speech-in-noise perception (Parbery-Clark et al, 2011, 2009).…”
Section: Introductionmentioning
confidence: 99%